Lack of IL-1 receptor signaling reduces spontaneous airway eosinophilia in juvenile mice with muco-obstructive lung disease - Brown, Ryan; Paulsen, Michelle; Schmidt, Simone; Schatterny, Jolanthe; Frank, Angela; Hirtz, Stephanie; Delaney, Rebecca; Doherty, Declan; Hagner, Matthias; Taggart, Cliff; Weldon, Sinéad; Mall, Marcus A. (American journal of respiratory cell and molecular biology, 2019)
Previous studies demonstrated spontaneous type 2 airway inflammation with eosinophilia in juvenile Scnn1b (sodium channel, non-voltage-gated 1, β-subunit)-transgenic (Scnn1b-Tg) mice with muco-obstructive lung disease. IL-1 receptor (IL-1R) signaling has been implicated in allergen-driven airway disease; however, its role in eosinophilic inflammation in muco-obstructive lung disease remains unknown. In this study, we examined the role of IL-1R signaling in the development of airway eosinophilia and type 2 inflammation in juvenile Scnn1b-Tg mice. We determined effects of genetic deletion of Il1r1 (IL-1 receptor type I) on eosinophil counts, transcript levels of key type 2 cytokines, markers of eosinophil activation and apoptosis, and tissue morphology in lungs of Scnn1b-Tg mice at different time points during neonatal development. Furthermore, we measured endothelial surface expression of intercellular adhesion molecule 1 (ICAM-1), an integrin involved in eosinophil transendothelial migration, and determined effects of eosinophil depletion using an anti-IL-5 antibody on lung morphology. Lack of IL-1R reduced airway eosinophilia and structural lung damage, but it did not reduce concentrations of type 2 cytokines and associated eosinophil activation in Scnn1b-Tg mice. Structural lung damage in Scnn1b-Tg mice was also reduced by eosinophil depletion. Lack of IL-1R was associated with reduced expression of ICAM-1 on lung endothelial cells and reduced eosinophil counts in lungs from Scnn1b-Tg mice. We conclude that IL-1R signaling is implicated in airway eosinophilia independent of type 2 cytokines in juvenile Scnn1b-Tg mice. Our data suggest that IL-1R signaling may be relevant in the pathogenesis of eosinophilic airway inflammation in muco-obstructive lung diseases, which may be mediated in part by ICAM-1-dependent transmigration of eosinophils into the lungs.
Gesehen am 30.03.2020